1991
DOI: 10.1002/ana.410300107
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging–based volume studies in temporal lobe epilepsy: Pathological correlations

Abstract: We performed a prospective study correlating magnetic resonance imaging volume measurements of the hippocampal formation with histopathology in 24 patients with intractable partial epilepsy who subsequently underwent an anterior temporal lobectomy for their seizure disorder. Patients with mass lesions verified pathologically were excluded from this study. In 71% of patients, quantitative hippocampal formation atrophy correctly lateralized the temporal lobe of seizure origin; in 29%, the volume study was indete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
189
2
5

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 443 publications
(211 citation statements)
references
References 14 publications
11
189
2
5
Order By: Relevance
“…13 In 1.5T MRI, a good correlation of volume and signal abnormalities detected by quantification analysis and histopathology of HS has been demonstrated. 29 More recently, histologic studies have proposed that different patterns of neuronal loss in the hippocampus might be associated with different seizure outcome after surgical removal of the temporal lobe. 30 Also, it has been shown that quantitative measures in 3T MRI can demonstrate ultrastructural details of HS pathology not detectable with lower field scanners.…”
Section: Discussionmentioning
confidence: 99%
“…13 In 1.5T MRI, a good correlation of volume and signal abnormalities detected by quantification analysis and histopathology of HS has been demonstrated. 29 More recently, histologic studies have proposed that different patterns of neuronal loss in the hippocampus might be associated with different seizure outcome after surgical removal of the temporal lobe. 30 Also, it has been shown that quantitative measures in 3T MRI can demonstrate ultrastructural details of HS pathology not detectable with lower field scanners.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological studies of TLE reveal that 30 to 40% of hippocampal specimens do not have classic MTS (at least 30-50% neuronal cell loss in hippocampal subfields CA1, CA3, and CA4) [24][25][26]. These specimens have either mild or limited neuronal loss and variable gliosis, or even no pathological change.…”
Section: Discussionmentioning
confidence: 99%
“…These specimens have either mild or limited neuronal loss and variable gliosis, or even no pathological change. MRI detects classic MTS (93% sensitivity and 100% specificity) [26]. Yet, approximately 50% of patients without hippocampal atrophy on MRI have good surgical outcomes [5,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence is accumulating to suggest that the prefrontal cortex is specifically involved in retrieval effort, with the medial temporal lobe system, in contrast, mediating the experience of conscious recollection (11). Patients with left temporal lobe epilepsy (TLE) show evidence of mesial temporal lobe hippocampal atrophy, as measured through magnetic resonance imaging (MRI) volumetry (16)(17)(18)(19)(20). Their deficits in explicit memory are well documented (21)(22)(23)(24)(25).…”
mentioning
confidence: 99%